Who designs local government performance measurement systems?. (14th May 2010) - Callanan, Mark
This article is a comparative analysis of the different actors behind the establishment and design of local government performance measurement systems. The article distinguishes between two broad approaches that can be discerned in identifying the origins of local government performance measurement systems. The first is where such systems are largely seen as a creature of higher levels of government, which they use to monitor the performance of local authorities. The second is where local government performance measurement systems are seen as creatures of local authorities themselves, initiated and designed by office-holders as a management tool or for communication purposes. The article argues that due to differing motives, the question of whether local government performance measurement systems are an initiative of local authorities themselves or of higher levels of government has a significant effect on the characteristics of the system.